Enhancing Learning Accessibility through Digital Libraries: A Study on User Orientation, Resources, and Pedagogical Aspects - Citra Rosalyn Anwar; Farida Febriati; Sella Mawarni; Muhammad Akbar Akhmad (Jurnal Edutech Undiksha, 2024)
The development of digital technology has driven the transformation of traditional libraries into digital formats to facilitate access to learning resources through internet networks. However, the effectiveness of digital libraries in meeting users' needs still requires comprehensive evaluation. This study aims to evaluate the effectiveness of an Android-based digital library platform used by students of the Educational Technology Study Program. The research employed a quantitative descriptive method with data collection techniques including questionnaires and interviews. The research instruments focused on three main aspects: user orientation, digital learning resources, and pedagogical aspects. The collected data were analyzed using descriptive statistics to measure the platform's effectiveness across these aspects. The findings revealed that the digital library platform received positive responses from students, with detailed results indicating an intuitive interface (90%), relevant learning resource collections (95%), good interactivity (85%), and support for collaborative learning (85%). These findings suggest that the Android-based digital library platform has been effective in providing access to learning resources and supporting students' learning processes. The conclusion of this study is that digital libraries can serve as an innovative solution to expand access to learning resources, enhance user engagement, and improve the effectiveness of educational processes in higher education settings.